2008
DOI: 10.1002/srin.200806344
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Fatigue Strength of Brazed, Locally Hardened Structures

Abstract: The advantages of low‐heat joining, such as low distortion and no appreciable influence on the local material properties as a result of the low heat input, should be utilized for improving the reliability of processes for the manufacture of high‐strength structures. For this purpose, the mutual interactions among the parameters of the joining process, the brazing‐seam geometry, the brazing filler, the type of stress, and the fatigue strength, especially for arc‐brazed structures, are the subject of investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…First comparative studies showed that the fatigue strength of bilateral brazed joints is up to 40 % higher than laser-welded seams without filler material. Additionally they have a stress amplitude which has a five times higher survival probability of the brazed seams [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First comparative studies showed that the fatigue strength of bilateral brazed joints is up to 40 % higher than laser-welded seams without filler material. Additionally they have a stress amplitude which has a five times higher survival probability of the brazed seams [4].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of hard-brazing include corrosion resistance, low distortion, and over all local material properties are hardly influenced, due to the low heat input. As a result the brazing process is appropriate for joining heat-sensitive and locally hardened structures [4,5]. These materials pass through a complex manufacturing process to get their locally defined properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The fatigue behavior was also intensively investigated in the thin sheet sector (see [2,3]). Sheet thicknesses from 0.8 to 2.4 mm were designed as various joint geometries and showed advantageous dynamic behavior compared to conventional welded joints.…”
Section: Introductionmentioning
confidence: 99%